Práticas de gestão democrática em escolas inovadoras - Santos, Alex Sandro Lucas dos (Universidade Federal de São Carlos, 2025)
This thesis investigates the interfaces between democratic management practices and school innovations in public basic education institutions in Brazil. The main objective was to analyze democratic management practices in order to assess their effects on pedagogical and curricular innovation, fostering a more inclusive and participatory environment. The research adopts a qualitative approach, grounded in content analysis. For data collection, semi-structured interviews were conducted with teachers, staff, coordinators, and principals from two schools recognized as innovative by the Programa de Estímulo à Criatividade e Inovação na Educação Básica (PECEB). The categories of analysis were defined a priori, in dialogue with the theoretical framework and research objectives: Democratic Management, Curricular Innovation, Community Participation, and School Climate/Methodologies. The results indicate that democratic management, supported by collegial bodies such as School Councils, Student Unions, and Parent-Teacher Associations, is essential for the implementation of pedagogical innovations. These innovations, in turn, foster an education that is more contextualized and adapted to local needs, expanding the autonomy of school agents and strengthening the school’s role as a mediator between the community and global knowledge. The study also identified challenges related to the sustainability of innovative practices, highlighting the importance of student protagonism and school leadership in consolidating meaningful changes. Finally, it suggests that educational policies should prioritize the integration between democratic management and curricular innovation to promote high-quality public education aligned with the principles of equity and social development.
Practices of democratic management in innovative schools
Keywords: Gestão Democrática; Inovação Curricular; Inovação Pedagógica; Conselhos de Escola; Direção Escolar; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade